FAO-fueled OXPHOS and NRF2-mediated stress resilience in MICs drive lymph node metastasis - Shan-Shan Li; Baifeng Zhang; Cuicui Huang; Yuying Fu; Yuying Zhao; Lanqi Gong; Yanan Tan; Huali Wang; Wenqi Chen; Jie Luo; Yu Zhang; Stephanie Ma; et al. (Proceedings of the National Academy of Sciences, 2025)
Metastasis is an inefficient process requiring cancer cells to adapt metabolically for survival and colonization in new environments. The contributions of tumor metabolic reprogramming to lymph node (LN) metastasis and its underlying mechanisms remain elusive. Through single-cell RNA sequencing, we identified rare metastasis-initiating cells (MICs) with stem-like properties that drive early LN metastasis. Integrated transcriptome, lipidomic, metabolomic, and functional analyses demonstrated that MICs depend on oxidative phosphorylation (OXPHOS) fueled by fatty acid oxidation (FAO) in the lipid-rich LN microenvironment. Mechanistically, the NRF2-SLC7A11 axis promotes glutathione synthesis to mitigate oxidative stress, thereby enhancing stress resistance and metastatic potential of MICs. Inhibition of NRF2-SLC7A11 reduced LN metastasis and sensitized tumors to cisplatin. Clinically, elevated NRF2-SLC7A11 expression was observed in tumors, with high expression correlating with LN metastasis, chemoresistance, and poor prognosis in esophageal squamous cell carcinoma (ESCC). These findings highlight the pivotal roles of FAO-fueled OXPHOS and NRF2 in LN metastasis and suggest targeting these pathways as a promising therapeutic strategy for metastatic ESCC.